Transient ischaemic attack: an exceptional presenting syndrome of a superior sagittal sinus thrombosis. (21st November 2013) - Scuotto, Assunta; D'Avanzo, Raffaele; Natale, Massimo; Rotondo, Michele
Abstract : We report a case of a transient ischaemic attack (TIA) as an exceptionally rare form of cerebral vein thrombosis. A 41-year-old man presented with a headache and five episodes of a transient left hemiparesis lasting approximately 10–15 min over the course of 2 weeks. Arterial origins of the disease were ruled out by detailed investigations. However, MR venography revealed a superior sagittal sinus thrombosis with numerous prominent collateral venous channels. No parenchymal lesion was seen. After medical therapy, no further transient neurological deficit occurred. Follow-up MR venography showed sinus recanalisation.